First record of the tribe Keroplatini from China, with descriptions of two new species (Diptera: Keroplatidae) - Xu, Huachao; Cao, Jian; Zhou, Zuji; Wu, Hong; Huang, Zhiwei (Zootaxa, 2007)
This is the first report of the tribe Keroplatini in China. Two new species are described: Platyroptilon wui, Cao, Xu et Evenhuis, n. sp. and Setostylus chinensis Cao, Evenhuis et Zhou n. sp. Another species, Heteropterna septemtrionalis (Okada), is newly recorded in China.